2022
DOI: 10.1017/s1368980022000672
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts of interest for members of the US 2020 dietary guidelines advisory committee

Abstract: Objectives: To measure incidence of conflicts of interest (COI) with food and pharmaceutical industry actors on the advisory committee for the 2020- 2025 U.S. Dietary Guidelines for Americans (DGA) and assess the adequacy of current mechanisms to disclose and manage COI among the committee’s members. Design: We compiled longitudinal data from archival sources on connections between members of the DGA’s advisory committee and actors. We hypothesed that these committee members, who oversee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…In addition, the food industry always had a strong influence on public opinion and dietary guidelines (Herman, 2010) as has been documented, for example, for Coca Cola (Sacks et al, 2017). Of the 20 members of the U.S. 2020 Dietary Guidelines Advisory Committee, 19 had conflicts of interest with the food and/or pharmaceutical industry, many of which are involved in the production of carbohydrate‐rich foods (Mialon et al, 2022). Thus, the scientific validity of dietary guidelines must be questioned, because they are not justified by high‐quality evidence, but influenced by the food industry, which makes a translation towards dietary needs of Neanderthals highly questionable.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the food industry always had a strong influence on public opinion and dietary guidelines (Herman, 2010) as has been documented, for example, for Coca Cola (Sacks et al, 2017). Of the 20 members of the U.S. 2020 Dietary Guidelines Advisory Committee, 19 had conflicts of interest with the food and/or pharmaceutical industry, many of which are involved in the production of carbohydrate‐rich foods (Mialon et al, 2022). Thus, the scientific validity of dietary guidelines must be questioned, because they are not justified by high‐quality evidence, but influenced by the food industry, which makes a translation towards dietary needs of Neanderthals highly questionable.…”
Section: Resultsmentioning
confidence: 99%
“…Overcoming industry relationship building is a complex strategy but with the aid of better science around policy networks analysis, and exposure and potential risk associated to those, can support efforts to better scrutinize actors close to the decision-making venues. 17 For instance, investigation around the connection and revolving doors of politicians and industry, has been effective in further accountability demands of claim-holders. 14,17 Furthermore, analyzing industry global commodity chains can expose how particular parts of the commodity chain have been exploited by corporate elites.…”
Section: Developing and Applying Mechanisms To Minimize Engagementmentioning
confidence: 99%
“…17 For instance, investigation around the connection and revolving doors of politicians and industry, has been effective in further accountability demands of claim-holders. 14,17 Furthermore, analyzing industry global commodity chains can expose how particular parts of the commodity chain have been exploited by corporate elites. 18 Surveillance and anger from food producer and peasant groups, key members of food production chains and largely ignored in the political economy of food corporations, have risen up against corporate actions and narratives.…”
Section: Developing and Applying Mechanisms To Minimize Engagementmentioning
confidence: 99%
“…An analysis of the 2020 DGAC subcommittee in charge of the saturated fat review found numerous intellectual, financial, and even religious conflicts of interest that may have contributed to a bias against saturated fats [ 51 , 52 ▪▪ ]. For instance, one member was found to have chaired five vegetarian conferences from 1997 to 2018, which might reflect a bias against saturated fats, since a more liberal policy towards these fats would inevitably allow for greater consumption of animal foods.…”
Section: Us Dietary Guidelines On Saturated Fatsmentioning
confidence: 99%